270 Evaluating Nutritional Strategies to Improve Performance of Poor Health Nursery Pigs. (7th May 2021) - Miller, Kayla A; Mendoza, Omarh; Shull, Caleb M; Hensch, Melissa; Gabler, Nicholas K
Abstract: Nursery pigs are frequently faced with disease challenges and producers are seeking nutritional strategies to help pig performance and health. Therefore, our objective was to evaluate five dietary formulation strategies that may improve performance in poor health nursery flow pigs (confirmed Rotavirus A and hemolytic E. coli positive at d 14). A total of 431 weaned pigs (5.5 ± 1.25 kg BW) were assigned to pens (10–11 pigs/pen) and one of five diets (n = 8 pens/treatment) over a 63-day test period consisting of 4 diet phases using a complete randomized design. In phase 1 and 2, treatments were: 1) 15–25% low soybean meal (LSBM), 2) 35–45% high soybean meal (HSBM), 3) 130% increase in valine and isoleucine branched-chain amino acids (BCAA) to Lys, 4) 2.1% combination of C8, C10 and C12 medium chain fatty acids (MCFA), and 5) 20% modified oats (MO). All pigs were fed a common diet for phases 3 and 4. Within phase, all diets were isocaloric with similar SID Lys:ME. Pen was considered the experimental unit and data were analyzed with contrast statements comparing each diet against the LSBM control. Across all phases, compared to LSBM, HSBM, BCAA and MO did not alter ADG, ADFI and G:F (P > 0.10). However, MCFA reduced (P < 0.05) ADG in phase 1 (0.20 vs 0.16 kg) and 2 (0.45 vs 0.39 kg) and phase 2 ADFI (0.66 kg vs 0.58 kg) compared to the LSBM treatment. Overall (0–63 days), compared to the LSMB, the MCFA treatment reduced ADG (0.46 vs 0.42 kg, P = 0.004) and ADFI (0.75 vs 0.68 kg, P = 0.009). Diet did not affect mortality. These data report that MCFA attenuated nursery pig performance, while HSBM, MO and BCAA diets fed in phases 1 and 2 had no longitudinal impact on pig performance or health.